Algorithm for forming a set of indicators of international trade customs regulation effectiveness in the EAEU member states - T. M. Vorotyntseva (Управление)
The relevance of the study is due to the fact that international trade globalization and intensification increase competitiveness of not only domestic but also foreign producers, so the business sector expects to facilitate business conditions, simplify customs procedures, increase customs activities efficiency, and improve customs services provision.   Goods transportation across the customs borders of countries around the world presents challenges in filling out documentation, transportation methods, information processing, and compliance with regulations that are not internationally harmonized. It leads to customs laws violations that must be detected during the customs control process. Consequently, customs regulation effectiveness will depend directly on the customs control results. The article presents a theoretical and methodological description of the procedure for assessing international trade customs regulation effectiveness in the EAEU member states, as well as a vector for developing a comprehensive set of performance indicators. The proposed assessment algorithm and the set of quantitative and qualitative indicators can be regarded as fundamental interrelated criteria that ensure improvement of efficiency of control over the customs authorities’ activities and corrective management decisions, if necessary. The application in customs practice of the proposed indicators for assessing international trade customs regulation effectiveness will contribute to customs policy effective implementation for the harmonious development of the EAEU member states’ economies, including Russia, in modern society and the basis of their sustainable political, economic and social development.